OF THE RIGHT TO TEST: AN ANALYSIS OF POSITIVE LEGAL DEVICES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article focuses on the will, regarding the legal effects of the extrajudicial opening of the will, with the purpose of analyzing and formulating a proposal for the extrajudicial opening of the will based on the consent of the heirs. The main concepts and constituent elements of the will will be presented and analyzed. Extrajudicial inventory is studied in the article from the perspective of two points. The first concerns the aspects of admissibility limits and the second concerns the aspects of regulatory limits. The extrajudicial inventory will be used as a procedural parameter for the proposal of the theme, considering that the will is conceptualized, above all, as a unilateral legal business based on the autonomy of the will. In turn, to strongly support the proposal of the article, it will be necessary to study the closed will, since this type of will aims to ensure the confidentiality of the expression of will of the testator. Then, the institutes of restriction and expansion of the highlighted theme will be analyzed. At the end of the elaboration of the contours and development of the text, the proposal will be made, focusing on the autonomy of the will of the heirs, backed by the principles of speed and procedural economy. Keywords: Testament; extrajudicial inventory; close will; extrajudicial opening of the will.